Diabetic testicular dysfunction and spermatogenesis impairment: mechanisms and therapeutic prospects - Zhang, Wenxiu; Tong, Li; Jin, Baofang; Sun, Dalin (Frontiers in Endocrinology, 2025)
With the global prevalence of diabetes mellitus (DM) steadily increasing, its impact on male reproductive health has become a growing area of concern. Diabetes-induced testicular damage involves alterations in testicular cell function, hormone levels, and the integrity of the blood-testis barrier (BTB), ultimately disrupting spermatogenesis. The key pathogenic factors include hyperglycemia, oxidative stress, chronic inflammation, mitochondrial dysfunction, and the accumulation of advanced glycation end products (AGEs).This review synthesizes the latest research on diabetes-induced testicular dysfunction and spermatogenic impairment, while also exploring potential therapeutic strategies. Current interventions are primarily focused on glycemic control, with supplementary treatments involving Chinese medicine, nanoparticles, and probiotics. Although most of the current evidence is derived from preclinical studies, these findings provide important insights that may inform future clinical research on diabetes-related male reproductive dysfunction.